Frações lábeis e recalcitrantes da matéria orgânica de solos da região semiárida potiguar - Santana, Josinaide Cláudia Araújo de (Universidade Federal Rural do Semi-Árido, 2019)
The search for socioeconomic sustainability of the farm is a great challenge, which involves, among other factors, good productivity in the present time and also, it allows the maintenance of its fertility, guaranteeing the agricultural production in the future. The use of soil organic matter (MOS) as an indicator of soil quality has been useful in the identification of the most sustainable forms of management, using as parameters total C levels and their soil fractions under native forest, however, this information is scarce for different types of soil. Thus, the objective of this study was to analyze labile and recalcitrant fractions of soil organic matter of diferente types of soil of the Rio Grande do Norte. For this, eight types of soils of different locations were selected, based on the material of origin, morphological, physical and chemical characteristics. The eigh soils were: Red-Yellow Latosol, Red-Yellow Argisol, Chernosol Rêndzico, Vertisol, all located in Mossoró/RN; Fluvic Neosol in Carnaubais/RN, two Haplic Cambisols in Afonso Bezerra/RN and Baraúna/RN, Red-Yellow Argisol in Apodi/RN. The collection of all the soils were under native forest in Hyperxerophilic Caatinga at depth 0-30cm and were analyzed physically and chemically. The values of total organic carbon (COT), labile carbon (CL) oxidized by KMnO4, and carbon in humic substances and their fractions humin, humic and fulvic acids were determined. The statistic used was the descriptive one, where the sample arithmetic mean was calculated and the variability of the means was estimated by its standard error. The high levels of calcium, clay and vegetable material contributed for the Chernosol Rêndzico had the highest of total organic carbon content (12,69 g kg-1), and C in the humic substances (11,83 g kg-1), especially in the humin fraction (11,25 g kg-1). In the soluble fractions of the humic substances, the highest levels of C in humic (1,27 g kg-1) and fulvic (2,37 g kg-1) acids were found in Red-Yellow Argisol in Apodi/RN, under limestone rocks, and in the labile fraction, the highest percentage of C (1,44 g kg-1) was found in Red-Yellow Latosol, being this fraction the one that contributed with 85.7% of the total organic carbon of this soil.
Monografia
Keywords: Bacia sedimentar; Substâncias húmicas; Carbono lábil; Carbono orgânico total; Sedimentary basin; Humic substances; Labile carbon; Total organic carbon; CIENCIAS AGRARIAS::AGRONOMIA